Serum proteomic profiling of post-COVID-19 syndrome by two-dimensional electrophoresis - Badhrulhisham, Aisyah; Mohamed Bakrim, Norbaiyah; Wan Ramli, Wan Nurliyana; Hamzah, Hairul Aini; Abdullah, Nor Zamzila; Abu Hassan, Salmah Anim; Muhamad, Dzawani; Idorus, Mohd Yusri; Khatib, Alfi (Faculty of Medicine, UKM, 2024)
Introduction: Post-COVID-19 Syndrome (PCS) presents with a wide range of symptoms affecting patients regardless of the severity of initial acute infection. The underlying mechanisms of PCS remain unclear, and diagnosis is typically made by exclusion, hence the discovery of diagnosis biomarkers for PCS is important. In this study, we aimed to examine serum PCS proteomic profiles to identify candidate protein biomarkers, thereby aiding in the prediction and diagnosis of this syndrome. Materials and method: Six PCS patients, 10 non-PCS (NPCS) patients; those who recovered from Covid-19 without lingering symptoms and 10 healthy controls (HC) aged 18 years and above, matched for gender and race were recruited. Serum from each group were pooled and proteins were separated using two-dimensional electrophoresis method. The protein spots on the gels were analysed by PD-Quest software focusing on identifying protein spots which were significantly differently expressed between the groups. These protein spots of interest then were identified using Matrix Assisted Laser Desorption/Ionization Time-of-Flight (MALDI-TOF) Mass Spectrometry. Results: The mean (SD) age for PCS patients was 38 (9.7) years, while persistent fatigue and cough were found to be most prevalent symptoms for PCS in our cohort. In the serum of PCS patients, among two proteins that significantly expressed were alpha-1 antitrypsin and albumin when compared to healthy controls. Additionally, two proteins namely haptoglobin and T-cell surface glycoprotein CD8 alpha chain were upregulated and three proteins identified as mannosyl-oligosaccharide glucosidase, immunoglobulin heavy constant alpha 1 and vitamin D-binding protein were downregulated in PCS in comparison to NPCS. Conclusion: Proteins that were significantly differently expressed in PCS patients mainly involve in the inflammatory and immunology pathways, indicating significant role of these mechanisms in the establishment of PCS and potential of these candidate proteins as biomarkers for PCS.